IMPROVING LEARNING OUTCOMES ON PLANE AREA THROUGH HOTS-ORIENTED PROBLEM BASED LEARNING (PBL) - Tika Fadilla Gusmiyati (CV Grasta Glory, 2026)
Students experience difficulty processing information provided by teachers, who typically use lectures. Students face challenges during the learning process due to varying levels of understanding. In mathematics, in particular, students struggle to understand and solve problems. This research aims to find out students' responses to learning using the HOTS-oriented PBL model, to find out the improvement in students' learning outcomes after implementing the HOTS-oriented PBL learning model, to find out the effectiveness of the PBL model on the HOTS-oriented area of ​​flat shapes material. This research uses a Classroom Action Research (CAR) design which is carried out in two cycles and involves fifth grade students at one of the Lubuklinggau Elementary Schools. Data collected through observation, test results, interviews and documentation. The research findings indicate that the implementation of the PBL model can increase student participation during the learning process and improve the average value of student learning outcomes from the pre-cycle to the second cycle. These results indicate that the PBL learning model is effective in improving students' mathematics learning outcomes. The implication of this study is that the PBL model can be recommended as an alternative learning strategy for teachers to create a more interactive, enjoyable, and student-centered mathematics learning environment. Further research can explore the application of PBL combined with digital media or test its effectiveness in other subjects.